AN ANALYSIS OF THE FORMS OF CODE MIXING ON FACEBOK STATUS USED BY ENGLISH STUDY PROGRAM STUDENTS AT BENGKULU UNIVERISITY IN ACADEMIC YEAR 2016/2017 - Sinci Lea Jeni Pratiwi; Dedi Sofyan; Imranuddin . (Universitas Bengkulu, 2018)
The aim of this research was to investigate the forms and the differences of code mixing by English Study Program students. The subject were four enrollments, they were 2nd, 4th, 6th, and 8th semester students. The object of this researcher was English Study Program student’s status on Facebook. This research used descriptive qualitative method. The instruments of this research were note and checklist. Technique of this research was documentation. The result of this research shows the English Study Program students used forms of code mixing such as; the insertion of word, the insertion of phrase, the insertion of hybrid, the insertion of word reduplication, the insertion of idiom, and the insertion of clause. Furthermore, there were the differences of using of code mixing by English Study Program students in each semester